Pattern of Health Promotion on Smokers Active to Stop Smoking Interest - M. Tata Suharta (Community Medicine and Education Journal, 2020)
Smoking is a cause of mortality and morbidity that can be prevented by the healthcare sector in high-income and middle-income countries. Indonesia ranks third in the list of ten countries with the largest population and consumption of cigarettes in the world after China and India in 2008 according to WHO and continues to increase. Health promotion is an effort to improve the ability of the community through learning from, by, for and with the community, so that they can help themselves, and develop community-based activities, in accordance with local social culture and supported by sound public policy. According to Ajzen and Fishbain, interest is a good predictor of smoking behavior in an individual. The theory of planned behavior (TPB) states that interest or intention is the closest determinant of behavior. The purpose of this study is to know the proportion of Sriwijaya University students who are interested to stop smoking, to know and analyze the dominant health promotion factors that influence the interest of active smokers to quit smoking and to determine health promotion pattern in active smokers to quit smoking. This research is an analytic research with cross sectional study design conducted at Sriwijaya University through distribution of questionnaire in November 2017. The sample of this research is active smokers in Sriwijaya University Palembang were taken by purposive sampling technique. The data obtained were analyzed by univariate analysis, chi square test, and multivariate logistic regression using IBM SPSS statistic version 22. This study obtained 392 respondents who match the inclusion criteria of 16 faculties. The results of statistical tests in this study found a significant relationship between students' interest to stop smoking with ever with the pattern of health promotion in the form of seminars and direct counseling mainly due to health factors, smoking frequency, age start smoking, medical personnel notice, doctor advice, family affection, and bad habits, with a value of p <0.05. The result of multivariate analysis showed that the most dominant health promotion pattern to play a role in the interest of quitting smoking on active smokers is promotion health health pattern. Each faculty should be able to make health promotion in the form of seminar or direct counseling to the community to get more comprehensive result.